Characterization of Urban New Particle Formation in Amman—Jordan - Tareq Hussein; Nahid Atashi; Larisa Sogacheva; Simo Hakala; Lubna Dada; Tuukka Petäjä; Markku Kulmala (Atmosphere, 2020)
We characterized new particle formation (NPF) events in the urban background of Amman during August 2016−July 2017. The monthly mean of submicron particle number concentration was 1.2 × 104−3.7 × 104 cm−3 (exhibited seasonal, weekly, and diurnal variation). Nucleation mode (10−15 nm) concentration was 0.7 × 103−1.1 × 103 cm−3 during daytime with a sharp peak (1.1 × 103−1.8 × 103 cm−3) around noon. We identified 110 NPF events (≈34% of all days) of which 55 showed a decreasing mode diameter after growth. The NPF event occurrence was higher in summer than in winter, and events were accompanied with air mass back trajectories crossing over the Eastern Mediterranean. The mean nucleation rate (J10) was 1.9 ± 1.1 cm−3 s−1 (monthly mean 1.6−2.7 cm−3 s−1) and the mean growth rate was 6.8 ± 3.1 nm/h (4.1−8.8 nm/h). The formation rate did not have a seasonal pattern, but the growth rate had a seasonal variation (maximum around August and minimum in winter). The mean condensable vapor source rate was 4.1 ± 2.2 × 105 molecules/cm3 s (2.6−6.9 × 105 molecules/cm3 s) with a seasonal pattern (maximum around August). The mean condensation sink was 8.9 ± 3.3 × 10−3 s−1 (6.4−14.8 × 10−3 s−1) with a seasonal pattern (minimum around June and maximum in winter).